Which Method Should I Select for My Legal Research – Doctrinal, Empirical, Multi-Method or Something Else? - Choudhary, Karan (Teisė, 2024)
This article scrutinises research methods for conducting research in the discipline of Law. Quality legal research, whether in the form of a research article, a thesis, a dissertation or any other, is a mere consequence of a meticulously planned research methodology. Protagonists of new research methods argue that renaissance in legal methods is needed to ensure the relevancy of Law as a subject in the present times, and also to find meaningful solutions to real life problems concerning Law. Traditionalists, however, vouch for the relevancy and continued importance of the traditional methods in legal research. Upon analysing various research methods, the author finds that the choice of research methods is contingent upon the understanding/perception of Law, and develops a visual representation of that idea. It has also been determined that research methods from social science are also being used in the legal research with the view to make the legal system more effective. The author argues for a multi-method legal research to arrive at more comprehensive output and to solve real life problems concerning Law.
Keywords: legal research; egal research methodology; Legal research methods; Multi-method legal research